Two-Component-System RspA1/A2-Dependent Regulation on Primary Metabolism in Streptomyces albus A30 Cultivated With Glutamate as the Sole Nitrogen Source - Zhang, Kuipu; Mohsin, Ali; Yu, Junxiong; Hu, Yuwen; Ali, Muhammad Fahad; Chen, Zhongbing; Zhuang, Yingping; Chu, Ju; Guo, Meijin (Frontiers in Microbiology, 2020)
A two-component system (TCS) RspA1A2 is identiﬁed and proved to play a positive role in the regulation of salinomycin (antibiotic) biosynthesis in Streptomyces albus. However, it is still unclear that how the RspA1A2 regulates carbon source (glucose or acetate) metabolism for cell growth of S. albus. Therefore, in this work, the mechanistic pathway of RspA1A2 on the carbon source metabolism is unveiled. Firstly, this work reports that the response regulator RspA1 gene rspA1 knockout mutant ΔrspA1 exhibits fewer biomass accumulation and lower glucose consumption rate as compared to the parental strain A30 when cultivated in a defined minimal medium (MM) complemented with 75mM glutamate. Further, it is demonstrated that the regulation of RspA1 of TCS RspA1A2 on the phosphoenolpyruvate-pyruvate-oxaloacetate node results in decreasing the intracellular acetyl-CoA pool in mutant ΔrspA1. Subsequently, it was verified that the RspA1 could not only directly interact with the promoter regions of key genes encoding AMP-forming acetyl-CoA synthase (ACS), citrate synthase (CS) and pyruvate dehydrogenase complex (PDH), but also could bind promoter regions of genes pyc, pck and glpX in gluconeogenesis. In addition, the transcriptomic data analysis showed that pyruvate and glutamate transformations supported robust two-component system RspA1A2-dependent regulation on glucose metabolism, which led to a decreased flux of pyruvate into TCA cycle and an increased flux of gluconeogenesis pathway in the mutant ΔrspA1. Finally, a new transcriptional regulatory network of TCS RspA1A2 on primary metabolism across central carbon metabolic pathways including glycolysis pathway, TCA cycle and gluconeogenesis pathway is proposed.